Peran Posyandu Remaja Terhadap Perilaku Kesehatan Reproduksi Remaja Di Posyandu Wilayah Puskesmas Trangkil Kota Pati Jawa Tengah - Rustiani, Desiana; Sutarno, Maryati (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Background: Teenagers are increasingly experiencing reproductive health issues, including unsafe abortions, HIV/AIDS, unintended pregnancies, and STDs. Naturally, the government needs to be concerned about these many issues because teens are valuable resources and the country's future. The UKBM Posyandu youth program is an attempt by the government to address a number of issues that teens face. Research Objective: To determine the role of adolescent Posyandu on adolescent reproductive health behavior in Posyandu in the Trangkil Community Health Center area, Pati City Central Java in 2023. Research Method: Quasy experimental with a population of all teenagers in the Posyandu working area of ​​the Trangkil Community Health Center, Pati City, as many as 32 people. The sample was determined using total sampling of 32 people. Research Results: Based on the results of the t test with the condition p<0.05, Ha is accepted and a significance level of 0.0001 is obtained. Based on OR, it can be seen that teenagers who attend youth posyandu are 25 times better regarding reproductive health behavior. Conclusions and Suggestions: There is an influence of the role of the Youth Posyandu on the Reproductive Health Behavior of Adolescents in the Posyandu in the Trangkil Community Health Center area, Pati City in 2023. The Posyandu is expected to increase promotion of the Youth Posyandu so that the number of teenagers participating in the Youth Posyandu program increases.